Prevalence Models to Support Participation: Sensory Patterns as a Feature of All Children’s Humanity - Dean, Evan E.; Little, Lauren; Tomchek, Scott; Wallisch, Anna; Dunn, Winnie (Frontiers in Psychology, 2022)
Purpose Research about children tends to consider differences from expected patterns problematic, and associates differences with disabilities [e.g., Autism, attention deficit hyperactivity disorder (ADHD)]. When we focus on disabilities and consider differences automatically problematic, we miss the natural variability in the general population. The International Classification of Functioning, Disability and Health (ICF 11) acknowledges that the experience of disability results from interactions between “environmental” and “personal” factors which determine the person’s capacity to participate. The purpose of this study was to examine sensory patterns across a national sample of children in the general population and samples of children with disabilities to investigate the extent to which differences in sensory processing are representative of natural variability rather than automatically problematic or part of a disability. Materials and Methods We employed descriptive statistics and chi-square tests to examine sensory processing patterns in children in the general population and autistic children and children with ADHD. We used standardization and validity data from the Sensory Profile 2 to conduct analyses. Results Consistent sensory patterns exist across all groups. Children in all groups had different rates of certain patterns. Conclusion Since children in all groups have certain sensory patterns, we cannot associate differences with problematic behaviors. Children participating successfully with all sensory patterns might provide insights for universal design that supports participation of all children.